Biological effects of gamma radiation on Galleria mellonella (L.) (Journal of Nuclear Technology in Applied Science, 2025)
The efficiency of gamma radiation doses was tested against some biological aspects  of the progeny of Galleria mellonella. Male and/or female full-grown pupae were  irradiated with 40, 100, 160, 200 and 260Gy. The results showed that the fecundity,  % egg hatchability, % pupation and adult emergence were negatively correlated  with the dose increase. On the other hand, % sterility, egg incubation period and  the larval duration were increased significantly (p
Keywords: Greater wax moth; Gamma radiation; Biological aspects; Sterility